2012
DOI: 10.1093/heapro/das055
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the implementation and efficacy of health-promoting schools via an action-research approach in Taiwan

Abstract: Taiwan launched its evidence-based health-promoting school (HPS) program via an action-research approach in 2010. The program featured a collaborative partnership between schools, local education authorities and university support networks. This study was focused on examining whether an HPS action-research approach was effective in advancing HPS implementation, perceived HPS impact and perceived HPS efficacy in Taiwan. In 2011, questionnaires were sent to 900 sample schools in Taiwan. A total of 621 schools re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Experts from universities participated in support network by providing technical support and local school action research training workshops to build teacher capacity and support implementation [ 74 ]. One study examined the support of the partnership program on continuous improvement for HP [ 74 ] and another assessed if the action research approach was effective in advancing HP implementation [ 75 ] ( micro-, meso- and exosystem ). In Hong Kong, HPS was first launched in 1998, and further developed as a Healthy Schools Award Scheme in 2001 with an aim to promote educational achievements, and to enhance the well-being of school students and staff [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experts from universities participated in support network by providing technical support and local school action research training workshops to build teacher capacity and support implementation [ 74 ]. One study examined the support of the partnership program on continuous improvement for HP [ 74 ] and another assessed if the action research approach was effective in advancing HP implementation [ 75 ] ( micro-, meso- and exosystem ). In Hong Kong, HPS was first launched in 1998, and further developed as a Healthy Schools Award Scheme in 2001 with an aim to promote educational achievements, and to enhance the well-being of school students and staff [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Forms of legislation and regulation were only identified in a few countries. Scotland had a legislative requirement for HPS to be integration in all schools (which was also accompanied by regular health and well-being inspections) [ 42 ], the United States has a legislative responsibility for all schools to have a wellness policy if they are participating in the national school lunch program [ 59 ] and Taiwan requires all schools to implement HPS [ 75 ]. Communication/marketing and fiscal policies were not explicitly described.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5] Countries such as India, Korea, Taiwan, Austria, the Lao People's Democratic Republic, 9 China, Hong Kong, Australia, and the Netherlands have prepared comprehensive school health checklists for evaluating the health profiles and conditions of HPS, and they have determined criteria according to the countries. [6][7][8][9][10][11][12][13] Mukoma and Flisher (2004) evaluated HPS, reporting that problems could be revealed by determining the appropriate methods in schools and that studies had shown positive advances in HPS. 4 In 1995, WHO provided a series of rules for schools that intended to gain the status of HPS.…”
mentioning
confidence: 99%